Konstantynopol nowym Heliopolis? Uwagi do „wizji” epoki konstantyńskiej w książce Rolfa Bergmeiera, Kaiser Konstantin und die wilden Jahre des Christentums. Die Legende vom ersten christlichen Kaiser, Aschaffenburg 2016 (zweite, korrigierte Auflage 2016), ss. 350. - Milewski , Ireneusz (Studia Europaea Gnesnensia, 2019)
This review paper focuses on Rolf Bergmaier’s book, which represents yet another contribution to the debate on the so-called Constantinian shift, a controversy which has engaged successive generations of historians of early Chris-tianity and late Roman Empire for over 150 years. Thus far, the available sources (texts and artefacts, including inscriptions, engraved gems and coins) enable historians to develop divergent visions of the Constantinian era, de-pending on sympathies and religious persuasion.